9p-3=5p+5

Simple and best practice solution for 9p-3=5p+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9p-3=5p+5 equation:


Simplifying
9p + -3 = 5p + 5

Reorder the terms:
-3 + 9p = 5p + 5

Reorder the terms:
-3 + 9p = 5 + 5p

Solving
-3 + 9p = 5 + 5p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-5p' to each side of the equation.
-3 + 9p + -5p = 5 + 5p + -5p

Combine like terms: 9p + -5p = 4p
-3 + 4p = 5 + 5p + -5p

Combine like terms: 5p + -5p = 0
-3 + 4p = 5 + 0
-3 + 4p = 5

Add '3' to each side of the equation.
-3 + 3 + 4p = 5 + 3

Combine like terms: -3 + 3 = 0
0 + 4p = 5 + 3
4p = 5 + 3

Combine like terms: 5 + 3 = 8
4p = 8

Divide each side by '4'.
p = 2

Simplifying
p = 2

See similar equations:

| 1/3(3x-9)=60 | | 6(3+x)=5(c-6) | | Z=12i | | 9(3y*3y)=10(3y) | | (x+9)(x+9)=648 | | 2+3x-3x^3=0 | | 1.1=logx | | 5x(squared)+43=x-1(5x+6) | | x^2+18x-567=0 | | 300=8990000000*(.0000000001/x) | | 300=8.99*10^9(.1*10^-9/x) | | 2x-9(-0)=14 | | 2(2r-1)=7(r+7) | | 8n-17=231 | | 5x+35=x+71 | | 3x^2+16x-48=0 | | R(x)=(x/x^2-49) | | -1/4(3x-5)=1/7(5-a)-2 | | 11(-10)-2y=-22 | | (a-13000)+a=81000 | | -2(3x-2)=3(-2-x) | | 2.5+0.5m=1+0.75m | | 2x^2+4x-b=0 | | 60/x=100 | | cos(2*(pi/4)) | | K+12=-10 | | M+-6=-10 | | 144=m+98 | | M+-3=-6 | | x^2+y^2+4x-3x-32=0 | | K+-11=12 | | 52+9=-21 |

Equations solver categories